Pengaruh Kualitas Pelayanan Terhadap Loyalitas Pada PD. BPR Bank Pasar Kebumen - Djoko Waluyo (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2020)
This study focuses on factors in service quality that affect customer loyalty in PD.BPR Bank Pasar Kebumen which includes tangible, reliability, responsiveness, assurance and empathy. The purpose of this study is to analyze the extent to which these factors affect customer loyalty. The analytical method used in this research is descriptive exploratory research method with quantitative and qualitative data analysis. For quantitative analysis in this study includes a general description of the company. While the qualitative analysis in this study used a questionnaire as an analytical aid with a sample of 75 respondents. Data analysis refers to the multiple linear regression formula (t test and F test), with the help of using the SPSS statistical program for Windows. The results showed that both partially and simultaneously, tangible variables, reliability, responsiveness, assurance and empathy had a significant effect on customer loyalty. Keywords: direct evidence (tangible), reliability (reliability), responsiveness (responsiveness), assurance (assurance) and empathy (empathy) and customer loyalty.